Adult pre B‐cell acute lymphoblastic leukemia with unusually large proportion of bone marrow CD45 bright/high SSc blasts. Issue 2 (14th December 2015) - Shahal‐Zimra, Yael; Rotem, Zohar; Chezar, Judith; Oniashvili, Nino; Leader, Avi; Raanani, Pia; Rabizadeh, Esther
Abstract : Background: We present a pre B‐ALL patient with the rare clinical manifestation of extramedullary disease, and a normal hemogram. This patient's blasts expressed bright CD45 and high side scatter (SSc) placing the cells in the monocyte gate. Methods: Samples from peripheral blood and bone marrow (BM) aspirate from a 50‐year‐old female patient were immunophenotyped by multiparametric flow cytometry. Results: Flow cytometry studies of the BM aspirate showed a large monocyte gate with 90‐95% of the cells expressing an abnormal B cell phenotype. Peripheral white blood cells count was normal and cytogenetic analysis of the BM revealed a normal karyotype. Conclusion: It was not possible, based on CD45/SSc to identify a lymphoblast population in this pre B‐ALL patient. Although bright expression of CD45 B‐ALL blasts has been associated with poor prognosis to the best of our knowledge, the combination of bright CD45 blasts with high SSc has not been reported. As CD45 expression vs. SSc is routinely measured in the diagnostics of acute leukemias, a possible association between CD45 bright positivity and extramedullary disease or prognosis warrants further exploration. © 2015 International Clinical Cytometry Society